2015
DOI: 10.1002/cmmi.1656
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpolarized 6Li as a probe for hemoglobin oxygenation level

Abstract: a Hyperpolarization by dissolution dynamic nuclear polarization (DNP) is a versatile technique to dramatically enhance the nuclear magnetic resonance (NMR) signal intensity of insensitive long-T 1 nuclear spins such as 6 Li. The 6 Li longitudinal relaxation of lithium ions in aqueous solutions strongly depends on the concentration of paramagnetic species, even if they are present in minute amounts. We herein demonstrate that blood oxygenation can be readily detected by taking advantage of the 6 Li signal enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…In dissolution DNP, superheated solvent such as water is rapidly injected into the frozen polarized sample, and the end result is the production of injectable liquids containing highly polarized nuclear spins . Using this technique, liquid‐state NMR signal enhancements of typically three to four orders of magnitude can be readily achieved for nuclei with low gyromagnetic ratio γ such as 13 C, 15 N, 6 Li, 89 Y, 107,109 Ag and others . With the advent of dissolution DNP, it has become feasible to use mainly hyperpolarized 13 C biomolecules as NMR and imaging (MRI) agents or tracers for in vitro and in vivo metabolic studies with excellent sensitivity and high specificity …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In dissolution DNP, superheated solvent such as water is rapidly injected into the frozen polarized sample, and the end result is the production of injectable liquids containing highly polarized nuclear spins . Using this technique, liquid‐state NMR signal enhancements of typically three to four orders of magnitude can be readily achieved for nuclei with low gyromagnetic ratio γ such as 13 C, 15 N, 6 Li, 89 Y, 107,109 Ag and others . With the advent of dissolution DNP, it has become feasible to use mainly hyperpolarized 13 C biomolecules as NMR and imaging (MRI) agents or tracers for in vitro and in vivo metabolic studies with excellent sensitivity and high specificity …”
Section: Introductionmentioning
confidence: 99%
“…[5] Using this technique, liquid-state NMR signal enhancements of typically three to four orders of magnitude can be readily achieved for nuclei with low gyromagnetic ratio γ such as 13 C, 15 N, 6 Li, 89 Y, 107,109 Ag and others. [5][6][7][8][9][10][11] With the advent of dissolution DNP, it has become feasible to use mainly hyperpolarized 13 C biomolecules as NMR and imaging (MRI) agents or tracers for in vitro and in vivo metabolic studies with excellent sensitivity and high specificity. [12][13][14][15][16][17][18] Optimized sample preparation is a critical aspect in DNP to achieve the highest NMR signal enhancement levels both in the frozen and liquid states.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of contrast material, hyperpolarized yttrium showed beneficial relaxation properties 5 , 6 and water protons were also hyperpolarized 7 10 . d-DNP studies with 107,109 Ag 11 , 6 Li 12 , 13 , 29 Si 14 , and 19 F 15 have been reported as well. However, to date, to the best of our knowledge, the phosphorus nucleus ( 31 P), which is 100% naturally abundant and plays an important role in chemistry and life, had not been seen in a d-DNP-driven hyperpolarized state in aqueous solutions.…”
Section: Introductionmentioning
confidence: 80%
“…A simple yet revolutionary method, pioneered by Ardenkjaer‐Larsen and coworkers, allows rapid dissolution of the frozen hyperpolarized sample from the polarizer and the subsequent transit of the resulting hyperpolarized solution to a nearby high‐resolution NMR spectrometer or magnetic resonance imaging scanner for analysis. Provided that the nuclei of interest have sufficiently long spin–lattice relaxation time T 1 , liquid‐state NMR signal enhancements of >10,000‐fold at room temperature are typically achieved for 13 C spins and other nuclei with low gyromagnetic ratio γ . More prominently, in vitro and in vivo NMR and magnetic resonance imaging using hyperpolarized 13 C biomolecules have enabled real‐time monitoring and imaging of metabolism with excellent sensitivity, specificity, and time resolution to interrogate a variety of diseases …”
Section: Introductionmentioning
confidence: 99%
“…Provided that the nuclei of interest have sufficiently long spin-lattice relaxation time T 1 , liquid-state NMR signal enhancements of >10,000-fold at room temperature are typically achieved for 13 C spins and other nuclei with low gyromagnetic ratio γ. [1,[6][7][8][9][10] More prominently, in vitro and in vivo NMR and magnetic resonance imaging using hyperpolarized 13 C biomolecules have enabled real-time monitoring and imaging of metabolism with excellent sensitivity, specificity, and time resolution to interrogate a variety of diseases. [11][12][13][14][15][16][17] Since its inception in 2003, dissolution DNP has become an increasing popular technique in academic and medical centers to solve the NMR sensitivity issue of low-γ nuclei or samples with low spin count.…”
Section: Introductionmentioning
confidence: 99%